The Development and Potential of Seaweed Tissue Culture - Beni Hendro Prabowo; Dedy Kurnianto; Ivana Riqoh Aprilia; Siti Amilia (Indonesian Journal of Biology Education, 2021)
Seaweed is widely used in many industries such as cosmetic foods, and drugs resulted in its increasing demand. To complete the market demand, it is necessary to escalate the seaweed cultivation. One of the problems of cultivation is the availability of the seed. The conventional and vegetative system of seaweed seed reproduction in the form of direct fragmentation or thallus cutting affects the degradation of seed quality. Therefore, another system of reproduction must be performed. One of the best ways to multiply the plants is tissue culture technique. Tissue culture is a plant multiplication technique using the artificial medium in a controlled and sterilized environmental condition. The advantage of this technique is the seeds will be all even, pathogen-free, numerous in one single production, and not influenced by any season. Some methods used in seaweed tissue culture are protoplasm culture, spore culture, and somatic embryogenesis. The government takes a serious action in seaweed industry by releasing the regulation of seaweed research and development through Presidential Regulation No. 33 of 2019 about the roadmap of National seaweed industry development 2018-2021. Therefore, the research and development of seaweed tissue culture is still widely open for its underexplored potential. On the other plants, this technique has reached the utilization stage to produce bioactive compounds e.g. the increasing production of saponin in Javanese ginseng callus culture. Based on that reason, the tissue culture technique can be implemented to search seaweed’s bioactive compound potential.